Association of autoimmune and allergic diseases with senile cataract: a bidirectional two-sample Mendelian randomization study - Yuan, Weichen; Li, Xiangrui; Wang, Guan; Qu, Bo; Zhao, Fangkun (Frontiers in Immunology, 2024)
Background: Many observational studies have been reported that patients with autoimmune or allergic diseases seem to have a higher risk of developing senile cataract, but the views are not consistent. In order to minimize the influence of reverse causality and potential confounding factors, we performed Mendelian Randomization (MR) analysis to investigate the genetic causal associations between autoimmune, allergic diseases and senile cataract.Methods: Single nucleotide polymorphisms associated with ten common autoimmune and allergic diseases were obtained from the IEU Open genome-wide association studies (GWAS) database. Summary-level GWAS statistics for clinically diagnosed senile cataract were obtained from the FinnGen research project GWAS, which consisted of 59,522 individuals with senile cataracts and 312,864 control individuals. MR analysis was conducted using mainly inverse variance weighted (IVW) method and further sensitivity analysis was performed to test robustness.Results: As for ten diseases, IVW results confirmed that type 1 diabetes (OR = 1.06; 95% CI = 1.05-1.08; p = 2.24×10 -12 ), rheumatoid arthritis (OR = 1.05; 95% CI = 1.02-1.08; p = 1.83×10 -4 ), hypothyroidism (OR = 2.4; 95% CI = 1.42-4.06; p = 1.12×10 -3 ), systemic lupus erythematosus (OR = 1.02; 95% CI = 1.01-1.03; p = 2.27×10 -3 ), asthma (OR = 1.02; 95% CI = 1.01-1.03; p = 1.2×10 -3 ) and allergic rhinitis (OR = 1.07; 95% CI = 1.02-1.11; p = 2.15×10 -3 ) were correlated with the risk of senile cataract. Celiac disease (OR = 1.04; 95% CI = 1.01-1.08; P = 0.0437) and atopic dermatitis (OR = 1.05; 95% CI = 1.01-1.10; P = 0.0426) exhibited a suggestive connection with senile cataract after Bonferroni correction. after multiple testing. These associations are consistent across weighted median and MR Egger methods, with similar causal estimates in direction and magnitude. Sensitivity analysis further proved that these associations were reliable.Conclusions: The results of the MR analysis showed that there were causal relationships between type 1 diabetes, rheumatoid arthritis, hypothyroidism, systemic lupus erythematosus, asthma, allergic rhinitis and senile cataract. To clarify the possible role of autoimmune and allergy in the pathophysiology of senile cataract, further studies are needed.